Sierra Leone : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Financing Assurances Review: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2012)
The discussions took place in Freetown during March 29-April 11, 2012; and in Washington (April 21-24, 2012). They focused on conditions for completing the fourth ECF review, corrective measures to be implemented to address fiscal slippages that had occurred in late 2011, and policies for the remainder of 2012. Key performance criteria for end-December 2011 were met. However, sizeable spending overruns resulted in a higher-than-programmed fiscal deficit, financed by an increase in unpaid bills. Implementation of structural reforms was mixed, with some measures postponed to 2012. The authorities implemented all prior actions agreed with staff during the fourth ECF review discussions. Staff recommends completion of the fourth ECF review and the review of financing assurances.